Reporting of Clinical Trial Interventions Published in Leading Otolaryngology–Head and Neck Surgery Journals. (20th November 2019) - Torgerson, Trevor; Johnson, Austin L.; Jellison, Sam; Tanghetti, Margo; Langley, Jean‐Maria; Nguyen, Lily H. P.; Vassar, Matt
Abstract : Objectives/Hypothesis: Randomized controlled trials (RCTs) play a crucial role in advancing patient care within otolaryngology–head and neck surgery (OTL‐HNS), yet studies have shown the reporting of these trials needs improvement. Here, we evaluate the completeness of intervention reporting of RCTs in OTL‐HNS and evaluate whether the publication of the Template for Intervention Description and Replication (TIDieR) checklist has influenced intervention reporting. Study Design: Retrospective Cross‐Sectional Analysis. Methods: We searched PubMed for RCTs published in top OTL‐HNS journals in two cohorts, one before the release of the TIDieR and one afterward. A sample of 300 RCTs was randomly selected and screened for inclusion. Once the dataset was finalized, we extracted trial characteristics and assessed each trial's adherence to the TIDieR checklist. We then used descriptive characteristics, a generalized estimated equation, time‐series analysis, and a two‐sample t test to analyze our data. Results: After screening was completed, 173 RCTs were included in our analysis. Of these RCTs, 103 (59.5%) showed <60% adherence to the TIDieR checklist. We found a slight increase in adherence to TIDieR items after the checklist was released, although this was not statistically significant ( P = .91). In addition, we found that trials with a crossover study design or multiple interventions and those that provided a Consolidated Standards for Reporting Trials statement were associated with greater adherence to the TIDieR checklist. Conclusions: The majority of OTL‐HNS RCTs included in our analysis showed suboptimal reporting factors related to the TIDieR checklist. Requiring a TIDieR statement and automating the journal requirements process for all OTL‐HNS clinical trials would be a worthwhile, efficient approach to improving research quality and ultimately patient care within OTL‐HNS. Level of Evidence: NA Laryngoscope, 130:E507–E514, 2020